2022
DOI: 10.3389/fped.2022.846301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stable Vagus Nerve Stimulation Efficacy on Autistic Behaviors in Ten Pediatric Patients With Drug Resistant Epilepsy: An Observational Study

Abstract: Vagus nerve stimulation (VNS) is a safe and effective therapy for pediatric patients with drug-resistant epilepsy (DRE). However, in children with DRE, the effects of VNS on autistic behaviors remain controversial. We retrospectively collected data from 10 children with DRE who underwent VNS implantation and regular parameter regulation in three pediatric epilepsy centers, and completed the behavioral assessments, including the autistic behavior checklist and the child behavior checklist, at follow-ups 1 (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This is in line with the previously proposed treatment protocol by Jaseja that recommends VNS implantation for the treatment of DRE in children with cerebral palsy to improve their neurocognitive de cits and QOL through its dual antiepileptic and IED-suppression therapeutic mechanism [11]. Another promising study reported that VNS has a positive role in modifying autistic behaviors in younger children with autism and DRE regardless of seizure control and in the absence of training interventions [32]. In contrast to our results, Tsai and his colleagues didn't nd any signi cant improvement in cognitive functions but mainly reduced seizure frequency and stress-related family dynamics [33].…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with the previously proposed treatment protocol by Jaseja that recommends VNS implantation for the treatment of DRE in children with cerebral palsy to improve their neurocognitive de cits and QOL through its dual antiepileptic and IED-suppression therapeutic mechanism [11]. Another promising study reported that VNS has a positive role in modifying autistic behaviors in younger children with autism and DRE regardless of seizure control and in the absence of training interventions [32]. In contrast to our results, Tsai and his colleagues didn't nd any signi cant improvement in cognitive functions but mainly reduced seizure frequency and stress-related family dynamics [33].…”
Section: Discussionsupporting
confidence: 86%
“…35 One key aspect of patient selection relates to recent discoveries that VNS has a myriad of effects—systemically and neurologically—which are only now becoming apparent. In addition to VNS′ well-documented and U. S. Food and Drug Administration–approved indication for depression, 36 early reports document therapeutic benefit in seemingly unrelated and comorbid disorders in patients with epilepsy including autism spectrum disorder, 37 obesity, 38 heart failure, 39 and rheumatoid arthritis. 40 As our understanding of the role of VNS in these and other disorders evolves, it will be important to consider these factors as well when identifying surgical candidates for VNS implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of ASD, such as stereotypic behaviors and di culties with mood and emotion recognition, are closely related to autonomic nervous system (ANS) dysfunction [31] . The ANS is a pathway system connecting the heart to the central nervous system, mediated by a variety of chemicals that maintain the body's ability to adapt acutely to stress, through parasympathetic and sympathetic stability to maintain homeostasis [32] .…”
Section: Discussionmentioning
confidence: 99%